Arab American Literary Fictions, Cultures, and Politics - Salaita, S. author. aut Link
XI, 196 p.
Keywords: N.B. this is a 'Palgrave to Order' title. Stock of this book requires shipment from overseas. It will be delivered to you within 12 weeks. Using literary and social analysis, this book examines a range of modern Arab American literary fiction and illustrates how socio-political phenomena have affected the development of the Arab American novel.